Study of Nuclear Structure for 36Si Isotope by Using Shell Model with Several Interactions (JOURNAL OF ADVANCES IN PHYSICS, 2020)
In this study, the nuclear shell model was applied to calculate the energy levels and reduced electric quadruple transition probability B(E2) for 36Si isotope using the OXBASH code within (1d3/2, 2s1/2, 2p3/2, 1f7/2) model space and using (HASN, ZBM2 and VPTH) interactions, As this isotope contains eight neutrons outside 28Si  core in the region and when comparing the results of this study with the values. Available process compatibility was acceptable. There was good agreement at level 2+1, and angular momentum and parity were confirmed for levels 4+, 6+, and for all interactions, and the value of B(E2) corresponds well with the only practical value available for the transition .